Relationships between throwing mechanics and shoulder distraction in professional baseball pitchers - Werner, S. L.; Gill, T. J.; Murray, T. A.; Cook, T. D.; Hawkins, R. J. (The American Journal of Sports Medicine, 2001)
The extreme forces and torques and the high speeds and excessive ranges of motion of baseball pitching place tremendous stress on the soft tissues of the throwing shoulder. Little is known about the relationship between pitching mechanics and shoulder joint stress, especially in professional athletes. The purpose of this study was to quantify joint loads and kinematic parameters of pitching mechanics at the major league level and to study their relationships. Three-dimensional, high-speed video data were collected on 40 professional pitchers during the 1998 Cactus League spring training. A clinically significant distraction force was calculated at the shoulder joint, which reached an average peak value of 947±162 N (108%±16% body weight). Descriptive statistics and a multiple linear regression analysis were used to relate shoulder distraction to kinematic and kinetic parameters of pitching mechanics. This study was undertaken not only to investigate the peak forces and torques on the shoulder, but also to identify potential areas of intervention that might prevent throwing injuries. Knowledge of joint ranges of motion, angular velocities, and joint-reaction forces can provide a scientific basis for improved preventive and rehabilitative protocols for baseball pitchers